ENSURING THE ELECTORAL RIGHTS OF CITIZENS DURING THE REGISTRATION AND COMPILATION OF VOTER LISTS - Abdurazakov Sultankhoja Suratovich (Scholar Express Journals, 2024)
This article examines the social relations developing in the field of the realization of the electoral rights of citizens of the Republic of Uzbekistan during elections. It is the exercise of citizens' electoral rights that ensures the sovereignty of the people, a democratic, political regime and control over the political elite by the population
Keywords: electoral law; ensuring the rule of law; ensuring the electoral rights of citizens